Innovative diamond‐like carbon coatings for the conservation of bronzes1. (29th January 2014) - Faraldi, Federica; Angelini, Emma; Riccucci, Cristina; Mezzi, Alessio; Caschera, Daniela; Grassini, Sabrina; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The research of new reliable materials and tailored conservation strategies to preserve metallic artefacts is the aim of this work. Diamond‐like carbon (DLC) thin films, deposited by plasma‐enhanced chemical vapour deposition (PECVD), could be considered as innovative, safe and reliable materials for the long‐term conservation of metals being PECVD an environmentally friendly process already widely used for the successful protection of metallic artefacts. Our previous researches revealed that DLC thin films deposited by PECVD are suitable candidates for the protection of archaeological artefacts, due to their chemical inertia and transparency. In the present work, the results obtained by evaluation tests of the protective properties of DLC coatings will be discussed, deposited on bronzes whose surface chemical composition, morphology and structural features are similar to those of the archaeological bronzes. An accelerated degradation methodology simulating the worst conditions suffered by the archaeological Cu‐based alloys has been purposely developed, and combined XPS and SEM‐EDS investigations have been carried out to validate the protective effectiveness of the DLC films. The obtained results reveal the potential use of the DLC films as protective barrier layers able to isolate the surface of metallic artefacts, limiting dangerous corrosion phenomena such as the copper cyclic degradation reaction defined as 'bronze disease'. Copyright © 2014 John Wiley & Sons, Ltd.